Eugenol Nanoparticles in Dental Composites: Literature Review of Antimicrobial, Anti-Inflammatory, and Clinical Applications - Fatima Zahra Kamal; Alin Ciobica; Gabriel Dascalescu; Said Rammali; Mohamed El Aalaoui; Radu Lefter; Ioana Vata; Vasile Burlui; Bogdan Novac (Microorganisms)
The formation of microbial colonies and biofilms are common on dental restorations. This can lead to secondary caries. Another common complication is the post-operative inflammation noted in patients. The traditionally used dental composites are designed without the inherent components having antimicrobial and inflammatory properties. This has become a major challenge in current restorative dentistry applications. In order to address these challenges, a possible approach is to incorporate eugenol nanoparticles (NPs) into dental composites. This approach can offer dual therapeutic benefits since eugenol possess both antimicrobial and inflammatory properties. In fact, compared to synthetic antimicrobial agents, eugenol exhibits antibacterial activity not only against Streptococcus mutans but also against a range of oral pathogens. It also exhibits anti-inflammatory effects that can promote healing by reducing post-operative sensitivity. In spite of the above benefits, eugenol cannot be incorporated directly into dental materials. This is because eugenol is highly volatile and has poor water solubility. The encapsulation of eugenol in suitable nano-materials can overcome these limitations. In addition, it can enable the controlled and sustained release of desirable agents for long-term therapeutic action. In this review, we explore the mechanisms, advantages and potential clinical applications of dental composites containing NP integrated with eugenol. We highlight the advantages of having antimicrobial and anti-inflammatory functions in a single restorative material. At the same time, we acknowledge the need for more in-depth research to optimize NP formulations with eugenol that does not compromise the mechanical properties of dental materials. Based on a thorough literature review, we believe that this approach has much potential in restorative dentistry procedures that will aid therapeutic outcomes in the future.